Checks And Balances Legislatif Eksekutif Terhadap Perjanjian Internasional Pasca Putusan MK No. 13/PUU-XVI/2018 - Nehru Asyikin (Universitas Widya Gama Malang, 2020)
The verdict of the Constitutional Court Judge states article 10 of the Law Number 24 year 2000 contrary to the Constitution and has no binding force of law, but conditional legislative approval only on the types of such agreements in article 10. The international Treaty of executives led to the paradigm of oversight and offset of executives against the implementation of international treaties into the national legal system, so the paradigm presents the principles of checks and balances. Legislative control lies in article 11 of paragraph 2 of the CONSTITUTION when the international treaty has an impact on the lives of people related to the financial burden of the State and its terms pursuant to article 10 of LAW Number 24 of 2000 concerning international treaties. While the president's right to issue presidential decree is only only an evaluation to the House of Representatives, it is interpreted as a process of assessing the prevailing norms in Indonesia so that the ratification by presidential decree is not denying but evaluating and returned to the president to be published in the Gazette of the country. As with the minister, the House of Representatives is positioned as a requested institution of consideration or consultation, the House of Representatives does not have the authority to cancel the policy to be taken by the Minister.